2014
DOI: 10.1007/s11164-014-1789-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of g-C3N4/BiOX (X = Cl, Br, I) composites, and their photocatalytic activity under visible light irradiation

Abstract: g-C 3 N 4 /BiOX (X = Cl, Br, I) composite photocatalysts have been prepared by means of a facile immersion-hydrolysis method. The microstructural and morphological characteristics of the as-prepared composite photocatalysts were investigated by means of X-ray diffraction, field emission scanning electron microscopy, transmission electron microscopy, and Fourier-transform infrared spectroscopy. The photodegradation performance of both g-C 3 N 4 /BiOCl and g-C 3 N 4 /BiOBr composites was superior to that of pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…However, the photocatalytic efficiency of single g-C 3 N 4 is limited due to the high recombination probability of photogenerated electron-hole pairs [5,6]. In order to improve photocatalytic activity, several efforts have been developed to improve the photocatalytic performance of g-C 3 N 4 in terms of introducing heteroatoms [7][8][9][10], sensitized by dyes [11], coupled with semiconductors or polymers [12][13][14][15][16], and controlling morphology [17][18][19]. Nevertheless, a simple development of highly efficient g-C 3 N 4 remains a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…However, the photocatalytic efficiency of single g-C 3 N 4 is limited due to the high recombination probability of photogenerated electron-hole pairs [5,6]. In order to improve photocatalytic activity, several efforts have been developed to improve the photocatalytic performance of g-C 3 N 4 in terms of introducing heteroatoms [7][8][9][10], sensitized by dyes [11], coupled with semiconductors or polymers [12][13][14][15][16], and controlling morphology [17][18][19]. Nevertheless, a simple development of highly efficient g-C 3 N 4 remains a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…it can be seen that BiOCl and CN are well attached and infiltrated on ZnO, leading to much rough surface which is favorable to the nucleation of light. It is worth noticing that BiOCl/ZnO exhibits intimate contact with CN and three constituents interact well to construct a distinctive heterojunction which is helpful to the transfer of charge carriers …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the surface area of carbon materials is high, which can increase the contact area between reactants and improve the photosynthetic efficiency. Literature [12] uses colloquial method to prepare carbon-containing yttrium oxychloride material, and analyzes its microstructure and morphology through X-ray diffractometer and a transmission electron microscope. Finally, it is found that adding carbon material can make carbon atom and yttrium oxychloride contact.…”
Section: Semiconductor -Yttrium Oxychloride Composite Modificationmentioning
confidence: 99%